Postoperative Bracing after Medial Patellofemoral Ligament Reconstruction - Schaver, Andrew L.; Tranovich, Meaghan A.; O'Reilly, Olivia C.; Bollier, Matthew J.; Duchman, Kyle R.; Wolf, Brian R.; Westermann, Robert W. (The Journal of Knee Surgery, 2024)
It is unclear if bracing is necessary after isolated medial patellofemoral ligament reconstruction (MPFLr) for recurrent patellar instability. We hypothesize that patients who did not use a brace will have similar outcomes to those who were braced postoperatively. A retrospective review of patients who underwent isolated MPFLr from January 2015 to September 2020 at a single institution was performed. Those with less than 6 weeks of follow-up were excluded. The braced group was provided a hinged-knee brace postoperatively until the return of quadriceps function, which was determined by the treating physical therapist (brace, “B”; no brace, “NB”). Time to straight leg raise (SLR) without lag, recurrent instability, and total re-operations were determined. Univariate analysis and logistic regression were used to evaluate outcomes (statistical significance, p < 0.05). Overall, 229 isolated MPFLr were included (B: 165 knees, 146 patients; NB: 64 knees, 58 patients). Baseline demographics were similar (all p > 0.05). Median time to SLR without lag was shorter in the NB group (41 days [interquartile range [IQR]: 20–47] vs. 44 days [IQR: 35.5–88.3], p = 0.01), while return to sport times were equivalent (B: 155 days [IQR: 127.3–193.8] vs. NB: 145 days [IQR: 124–162], p = 0.31). Recurrent instability rates were not significantly different (B: 12 knees [7.27%] vs. NB: 1 knee [1.56%], p = 0.09), but the re-operation rate was higher in the brace group (20 knees [12.1%] vs. 0 [0%], p = 0.001). Regression analysis identified brace use (odds ratio [OR]: 19.63, 95% confidence interval [CI]: 1.43–269.40, p = 0.026) and female patients (OR: 2.79, 95% CI: 1.01–7.34, p = 0.049) to be associated with needing reoperation. Recurrent instability rates and return to sport times were similar between patients who did or did not use a hinged knee brace after isolated MPFLr. Re-operation rates were higher in the braced group. Retrospective Comparative Study, Level III
Keywords: patellar instability; MPFL reconstruction; bracing; rehabilitation